(untitled) (Baghdad Science Journal, 2025)
The induced photodegradation of methyl cellulose (MC) films in air was investigated in the absence and presence of aromatic carbonyl compounds(photosenssitizers): 1,4-naphthaquinone (NQ) and benzophenone (BPH) by accelerated weathering tester. The addition of (0.01 wt %) of low molecular weight aromatic carbonyl compounds to cellulose derivatives films(25µm in thickness) enhanced the photodegradation of the polymer films.The photodegradation rate was measured by the increase in carbonyl absorbance. Decreases in solution viscosity and reduction of molecular weight were also observed in the irradiated samples. Changes in the number-average chain scission, the degree of deterioration and in the quantum yield of chain scission values are also observed, and it was concluded that branching or cross-linking has occurred for cellulose derivative with NQ and BPH. Findings from all analytical techniques indicated that the 1,4-naphthaquinone (NQ) photosensitizer enhance the photodegradation of methyl cellulose more than benzophenone (BPH). The effect of the photosensitizer concentration, (ranging from 0.01 to 0.1 %), on the rate of photodegradation was also monitored for MC films. The rates are increased with increasing the photosensitizer concentration. The effect of film thickness is also studied at fixed sensitizer concentration (0.05%), and results show that the rate of cellulose derivative photodegradation decreases with increasing film thickness. The rate constants of the photodegradation of the photosensitizers deduced in cellulose derivatives films, [at concentration of (0.1%)by weight and thickness (25µm)]. Biodegradation of irradiated cellulose derivatives films was conclusively established with bacteria type Pseudomonas aeuroginosa Rb-19 isolated from crude oil. The amount of bacteria growth on MC after 30 days was lower, while there was no growth observed in MC with BPH